2012
DOI: 10.2174/156800912803251180
|View full text |Cite
|
Sign up to set email alerts
|

LRRC4 Inhibits Glioma Cell Growth and Invasion Through a miR-185- Dependent Pathway

Abstract: Leucine-rich repeat (LRR) genes encode transmembrane proteins that are essential for normal brain development and are often dysregulated in central nervous system tumors. Leucine-rich repeat C4 (LRRC4) is a member of the LRR protein superfamily and specifically expressed in brain tissue. Importantly it acts as a tumor suppressor in the pathogenesis of malignant gliomas. However, the molecular mechanisms by which LRRC4 regulates glioma tumorigenesis are largely unknown. In this report, we found that miR-185 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Our previous study showed methylation status before and after the development of a carcinoma in 3 cases of nasopharyngeal precancerous lesions; we found that there is substantial methylation of the LRRC4 gene promoter region after the development of nasopharyngeal carcinoma, and there is a large number of methylation peaks in the sequence. Studieson brain glioma also showed that aberrant methylation of the LRRC4 promoter is an important mechanism behind the lack of LRRC4 expression in glioma cells (Zhang et al, 2009;Tang et al, 2012). The present result suggests that the substantial methylation of the upstream region of the LRRC4 promoter abrogates the LRRC4 expression in nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…Our previous study showed methylation status before and after the development of a carcinoma in 3 cases of nasopharyngeal precancerous lesions; we found that there is substantial methylation of the LRRC4 gene promoter region after the development of nasopharyngeal carcinoma, and there is a large number of methylation peaks in the sequence. Studieson brain glioma also showed that aberrant methylation of the LRRC4 promoter is an important mechanism behind the lack of LRRC4 expression in glioma cells (Zhang et al, 2009;Tang et al, 2012). The present result suggests that the substantial methylation of the upstream region of the LRRC4 promoter abrogates the LRRC4 expression in nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…Low expression of miR-185 is also associated with a poor outcome in glioma patients. miR-185 was found to suppress glioma cell invasion, indicating that it may be a potential prognostic marker and therapeutic target (16). Previous studies have revealed that miR-185 impedes anchorage-independent growth, cell migration and invasion, in addition to suppressing tumor growth in vivo and increasing cisplatin sensitivity by promoting apoptosis, implicating it as a potent tumor suppressor (17)(18)(19).…”
Section: Discussionmentioning
confidence: 98%
“…ISH procedures were carried out as previously described (20). miR-200b and miR-200c miRCURY LNA custom detection probes (Exiqon) were used for ISH.…”
Section: Ish Analysismentioning
confidence: 99%
“…The cell invasion assay was conducted as described previously (20). Briefly, cells were seeded onto the basement membrane matrix present in the insert of a 24-well culture plate (EC matrix; Chemicon).…”
Section: Cell Invasion and Migration Assaysmentioning
confidence: 99%